Reconstructing Hydrothermal Fluid Pathways and Storage at the Solfatara Crater (Campi Flegrei, Italy) Using Seismic Scattering and Absorption - Di Martino, Maria Del Pilar; De Siena, Luca; Serlenga, Vincenzo; De Landro, Grazia (Frontiers in Earth Science, 2022)
Imaging of fluid pathways is crucial to characterize processes taking place in hydrothermal systems, a primary cause of volcanic unrest and associated hazards. The joint imaging of seismic absorption and scattering is an efficient instrument to map fluid flow at crustal scale, and specifically in volcanoes; however, this technique has so far been applied to image volcanoes and hydrothermal systems at the kilometre scale. Here, we use data from a meter-scale, active seismic survey inside the shallow structure of the Solfatara crater to obtain the first frequency-dependent near-surface scattering and absorption model of a hydrothermal system. The Solfatara crater is the place used to monitor historic unrest at Campi Flegrei caldera (Italy), a high-risk volcano under continuous surveillance due to its closeness to a densely populated area. Improving the imaging of the shallow part of this system is crucial to broaden the understanding of unrest processes that are progressively characterizing other portions of the eastern caldera. The scattering contrasts highlight the primary structural feature, a fault separating the hydrothermal plume from zones of CO2 saturation nearing fumaroles. While high-absorption anomalies mark zones of high soil temperatures and CO2 fluxes, low-absorption anomalies indicate zones of very shallow upflow and are caused by contrasts between liquid-rich and vapour-rich fluids coming from mud pools and fumaroles, respectively. All maps show a SW-NE trend in anomalies consistent with fluid-migration pathways towards the eastern fumaroles. The results provide structural constraints that clarify mechanisms of fluid migration inside the crater. The techniques offer complementary geophysical images to the interpretation of hydrothermal processes and prove that seismic attenuation measurements are suitable to map fluid pathways in heterogeneous media at a detailed scale.